2020
DOI: 10.1007/s00277-020-04246-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the continuing medical education needs of US physicians in the management of patients with beta thalassemia

Abstract: Patients with beta thalassemia are benefitting from longer life expectancies, highlighting the importance of appropriate transition from pediatric to adult care. Data are limited regarding continuity of care and adult hematologists' management of patients with beta thalassemia. We conducted a survey of practicing US hematologists to identify practice gaps, attitudes, and barriers to optimal patient management among US-practicing hematologists. A total of 42 responses were collected, with 19 (45%) practicing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The costs associated with thalassemia treatment are often significant and go beyond medical treatment, including transportation costs for routine care, nutritional supplements, and loss of income due to frequent absences from work. In this study, many parents expressed concern about the ongoing financial burden, which is compounded by the lack of insurance coverage or financial support from the government (Behdani et al, 2015;Stacy et al, 2021). Previous research has identified that access to affordable healthcare is a determining factor in the successful management of pediatric chronic diseases (Stacy et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…The costs associated with thalassemia treatment are often significant and go beyond medical treatment, including transportation costs for routine care, nutritional supplements, and loss of income due to frequent absences from work. In this study, many parents expressed concern about the ongoing financial burden, which is compounded by the lack of insurance coverage or financial support from the government (Behdani et al, 2015;Stacy et al, 2021). Previous research has identified that access to affordable healthcare is a determining factor in the successful management of pediatric chronic diseases (Stacy et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…The key is helping adult providers gain confidence in the nuanced care of adult patients through continuing education 21 . There are several easily accessible, on‐demand webinars and grand rounds covering various topics related to thalassemia management offered by the Cooley's Anemia Foundation, the Thalassemia International Federation as well as continuing medical courses sponsored by industry partners.…”
mentioning
confidence: 99%
“…As a result, patients are compelled to advocate for their needs as the doctors tasked with their care may not understand their transfusion requirements, the nuances of chelation therapy, or the inherent risk of comorbidities. [20][21][22] Balancing the normal challenges of adulthood with the demands of living with a rare genetic blood disorder is difficult enough without the added struggle of trying to find a provider who is competent in our care. 23 Since I outgrew my pediatrician (who was also my pediatric hematologist), I have not had a consistent primary care provider (PCP).…”
mentioning
confidence: 99%
See 2 more Smart Citations